Genre-based translation strategies on cultural references: a systematic review - Zhu, Hongxiang; Ang, Lay Hoon; Mansor, Nor Shahila (Journal of Language and Linguistic Studies, 2022)
Cultural references refer to the lexical items that either do not exist in the target culture or deviate in denotation or connotation from lexical equivalents in the target culture. Translating cultural references poses challenges for translators since these references are gaps in specific target culture. This systematic review aims to examine what strategies are adopted on translating cultural references in different genres. A systematic literature search was conducted using Web of Science and Scopus databases. Source (articles) published up to the 31 October 2021 were included. The genres were categorized into literary texts, audiovisual translation and Others, such as newspapers and tourism texts translation. A total of 72 studies were identified with the help of flow diagram of Page et al.’s (2021) Preferred Reporting Items for Systematic reviews and Meta-Analyses. The review revealed that: (1) More studies focused on literary texts while non-literary translation is relatively less; (2) The application of taxonomies of translation strategies on cultural references had crossed the boundaries of genres but confined into two genres; (3) There was no one-size-fits-all classification for cultural reference translation; (4) The taxonomies mostly followed the trend from foreignization to domestication. In conclusion, more studies of translation strategies on cultural references are required from non-literary genres and the consolidated strategy taxonomy is needed to solve the specific problem. This review study could help the translators and scholars to have a better understanding of the translation strategies on cultural references.